Toxicity of ubiquitous tire rubber antiozonant N-(1,3-dimethylbutyl)-N′-phenyl-p-phenylenediamine (6PPD) and its transformation product 6PPD-quinone (6PPD-Q) in primary human hepatocytes and liver spheroids - Daniel J. Yeisley; Lijun Ren; Katy S. Papineau; Laura K. Schnackenberg; Gonçalo Gamboa da Costa; Tucker A. Patterson; Suzanne C. Fitzpatrick; Qiang Shi (Biochemistry and Biophysics Reports)
The tire rubber antioxidant N-(1,3-dimethylbutyl)-N′-phenyl-p-phenylenediamine (6PPD) and its oxidation product 6PPD-quinone (6PPD-Q) were recently found in human bodies. Though 6PPD/6PPD-Q showed species-dependent toxicity in animals, human relevant data are scarce. Here, primary human hepatocytes (PHHs), the gold standard in vitro model for hepatotoxicity, were used for acute and subacute toxicity assessments, with test concentrations normalized to average human serum concentrations (Cave). Acute exposure in sandwich cultured PHHs decreased glutathione starting at 100-fold Cave of 6PPD (10 ng/mL) or 500-fold Cave of 6PPD-Q (100 ng/mL), and inhibited albumin starting at 10,000-fold Cave of 6PPD, or 2500-fold Cave of 6PPD-Q. Urea was suppressed by 6PPD-Q, but not 6PPD, starting at 2500-fold Cave. Lactate dehydrogenase (LDH) leakage, a measurement of cell death, was unaffected. Subacute exposure of primary human liver spheroids to 6PPD-Q showed no cell death, while 6PPD increased caspase 3/7 activity and LDH leakage and decreased adenosine triphosphate at 50,000-fold Cave. Of 10 cytokines involved in hepatotoxicity, interleukin-8 was increased by 6PPD and 6PPD-Q starting from 200- and 50-fold Cave, respectively. At 50 to 300-fold Cave, the in vivo-relevant concentrations in humans, GSH, caspase 3/7 activity, and interleukin-8 were the only endpoints that were significantly affected by 6PPD and/or 6PPD-Q, and no cell death was observed. These data indicate that 6PPD/6PPD-Q may cause liver dysfunctions and trigger immunotoxicity in heavily exposed individuals but are unlikely to induce significant cell death at regular environmental exposure levels.